Anatomie de l'enfer: La physicalité de la damnation éternelle dans l'Italie de la Contre-Réforme - Al Kalak, Matteo (Revue de l'histoire des religions, 2023)
In relation to scholarship on the construction of the Christian afterlife, this research focuses on two works that codified the infernal underworld in the Italian context at the beginning of the Counter-Reformation. In particular, the book La grandezza et larghezza et distanza di tutte le sfere by the humanist Giovanni Maria Bonardo († 1590) and the treatise De inferno et statu daemonum, by the Milanese theologian Antonio Rusca († 1655), are considered. Bonardo’s book presents a hell placed at the centre of an Aristotelian-Ptolemaic universe, with calculated and precise dimensions. Rusca’s book, on the other hand, examines the location of the kingdom of evil with an entirely theological approach. From the comparison between the two works emerges the indispensability of the physical dimension of hell from the Catholic perspective. In conclusion, a possible categorization of the models of hell developed at the beginning of the modern era is proposed.